2009
DOI: 10.1007/s15010-009-8116-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous vs thrice-daily ceftazidime for elective intravenous antipseudomonal therapy in cystic fibrosis

Abstract: We conclude that continuous or thrice-daily dosing of intravenous ceftazidime, both combined with once-daily tobramycin, are equally effective application regimens for elective antipseudomonal therapy in clinically stable patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
1
22
0
6
Order By: Relevance
“…Giving the same daily dose as a short-term infusion q6h instead of q8h achieved only a PK-PD MIC breakpoint of 2 mg/liter in CF patients. This prediction is in excellent agreement with the better outcome for CF patients with resistant or intermediate isolates when they received continuous ceftazidime infusion compared to when they received short-term infusion (both coadministered with tobramycin) (36,63) and with results from in vitro PD models (1,20,51).…”
Section: Discussionsupporting
confidence: 64%
“…Giving the same daily dose as a short-term infusion q6h instead of q8h achieved only a PK-PD MIC breakpoint of 2 mg/liter in CF patients. This prediction is in excellent agreement with the better outcome for CF patients with resistant or intermediate isolates when they received continuous ceftazidime infusion compared to when they received short-term infusion (both coadministered with tobramycin) (36,63) and with results from in vitro PD models (1,20,51).…”
Section: Discussionsupporting
confidence: 64%
“…Riethmueller et al, found a decrease in WCC favouring CI of ceftazidime in cystic fibrosis patients [364]. However, the differences obtained in the randomized crossover study were insignificant when compared to IB (CI; -2216 versus IB; 2209, p = 0.98).…”
Section: Mortalitymentioning
confidence: 91%
“…Riethmueller et al, compared anti-infectious properties of CI and thrice-daily administration of ceftazidime in 56 cystic fibrosis patients in a randomized crossover study [364]. The authors found no significant difference between the two methods in terms of decrease in leukocyte counts, clinical, lung function and inflammatory parameters.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations